Spontaneous resolution of myopic foveoschisis and a macular hole with retinal detachment - Takashi Ono; Yukiko Terada; Yosai Mori; Yasushi Kataoka; Masaaki Nakahara; Kazunori Miyata (American Journal of Ophthalmology Case Reports, 2019)
Purpose: The aim of this report was to describe a case of myopic foveoschisis and a macular hole with retinal detachment that resolved spontaneously. Observations: A 62-year-old woman with bilateral blurred vision was referred to our department. Her best-corrected visual acuity (BCVA) was 0.4 bilaterally; the standard equivalent refractive error was −17.0 diopters in the right eye and −18.75 diopters in the left eye. The axial length was 31.4 mm and 31.2 mm, respectively. After cataract surgery was performed, the BCVA of the right and left eye was 0.6 and 1.0, respectively. Four years later, slight macular traction, foveoschisis, and the macular hole had progressed in the left eye and the BCVA had decreased to 0.7. However, the macular hole had closed, the foveoschisis had resolved, and retinal detachment had mostly resolved three weeks later. The BCVA improved to 0.8. The macular hole did not reoccur and retinal detachment resolved completely after six more months. Conclusions and Importance: This case demonstrated that myopic foveoschisis and a macular hole with retinal detachment could improve spontaneously. It is necessary to decide carefully whether surgery is required or whether the patient should be observed. Keywords: Macular hole, Myopic foveoschisis, Retinal detachment, High myopia